Sexual harassment: liability of sexual harasser and employer in tort - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Ahmad, Abubakar Aminu; Ahmed, Kyaw Hla Win @ Md Hassan (Universiti Putra Malaysia Press, 2015)
Sexual harassment conducts such as patting, pinching, constant brushing or touching an inappropriate area of another person’s body, making sexually-related comments, jokes and graphic drawing, making degrading comments on one’s appearance and displaying sexually suggestive pictures, among others, are examples of situations in which the honour and dignity of an employee is violated. Such conduct, if allowed to go unchecked, would create an ‘intimidating, hostile and offensive work environment that can adversely affect the industrial relations climate in the organisation’. In most cases, the victims get annoyed, angry and even embarrassed by the unwanted sexual attention, as it belittles their person. The aggrieved worker may experience emotional trauma, anxiety, nervousness, depression and low self-esteem. Further, it may also affect the employee’s morale and job performance such as causing difficulty in concentrating on the job. Employers may avoid liability if they exercise reasonable care to prevent or correct promptly any harassing behaviour. If a co-worker is involved, employers are generally liable if they knew or should have known of the misconduct, unless they can show that they took immediate and appropriate corrective action. Further, failure to respond to bona fide complaints of sexual harassment would constitute a breach of the implied trust and confidence term. In the aforesaid breach the aggrieved employee may resign and claim constructive dismissal. This paper explores the possible causes of action in tort against the assailant and the employer of the aggrieved worker for general and specific damages for the alleged assault and battery arising from incidents of sexual harassment.